The Influence of Gender and Investment on Economic Growth in Sumatra - Pamelia, Vania; Ratih, Arivina (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the impact of gender equality and domestic investment on economic growth in Sumatra from 2017 to 2022. Specifically, it examines the roles of the Gender Development Index (GDI), Gender Empowerment Index (GEI), and Domestic Investment (PMDN) using secondary data sourced from BPS. The research employs panel data regression analysis to identify significant factors influencing economic growth. The results reveal that both GDI and GEI have a positive and significant effect on economic growth, while PMDN also contributes positively. These findings highlight the importance of promoting gender equality and boosting domestic investment to drive economic development. Additionally, the study identifies diverse economic behaviors across provinces, indicating the necessity for tailored regional development strategies. Overall, this research underscores the critical role of gender equality and investment in fostering sustainable economic growth in Sumatra.